In vitro exposure of Ulva lactuca Linnaeus (Chlorophyta) to gasoline: biochemical and morphological alterations - Pilatti, Fernanda Kokowicz (2016)
Refined fuels have considerable share of pollution of marine ecosystems. Gasoline is one of the most consumed fuel worldwide, but its effects on marine benthic primary producers are poorly investigated. In this study, Ulva lactuca was chosen as a biological model due to its cosmopolitan nature and tolerance to high levels and wide range of xenobiotics and our goal was to evaluate the effects of gasoline on ultrastructure and metabolism of that seaweed. The experimental design consisted of in vitro exposure of U. lactuca to four concentrations of gasoline (0.001%, 0.01%, 0.1%, and 1.0%, v/v) over 30 min, 1 h, 12 h, and 24 h, followed by cytochemical, SEM, and biochemical analysis. Increase in the number of cytoplasmic granules, loss of cell turgor, cytoplasmic shrinkage, and alterations in the mucilage were some of the ultrastructural alterations observed in thalli exposed to gasoline. Decrease in carotenoid and polyphenol contents, as well as increase of soluble sugars and starch contents were associated with the time of exposure to the xenobiotic. In combination, the results revealed important morphological and biochemical alterations in the phenotype of U. lactuca upon acute exposure to gasoline. This seaweed contain certain metabolites assigned as candidates to biomarkers of the environmental stress investigated and it is thought to be a promise species for usage in coastal ecosystems perturbation monitoring system. In addition, the findings suggest that U. lactuca is able to metabolize gasoline hydrocarbons and use them as energy source, acting as bioremediator of marine waters contaminated by petroleum derivatives.